2007
DOI: 10.1007/s00464-006-9131-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mechanical strength and patency of functional end-to-end anastomoses

Abstract: The bursting pressure of the mechanical staple line using the EndoGIA 60 stapler was the strongest. Functional end-to-end anastomosis was stronger when created with buttress of an anastomotic crotch, and larger circumferences were created with the wide technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
0
19
1
Order By: Relevance
“…The optimal formation rate in the top aspect was lower than that in the root completed without proper devices [11,12]. Although the surgical techniques to ensure a satisfactory blood supply and no tension to the anastomotic site are essential, correct usage of the proper devices also is important to prevent anastomotic failure [6][7][8][9][10]. However, only a few studies have described the proper use of linear suturing devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal formation rate in the top aspect was lower than that in the root completed without proper devices [11,12]. Although the surgical techniques to ensure a satisfactory blood supply and no tension to the anastomotic site are essential, correct usage of the proper devices also is important to prevent anastomotic failure [6][7][8][9][10]. However, only a few studies have described the proper use of linear suturing devices.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described how to improve outcomes after mechanical anastomosis [6][7][8][9][10]. However, to our knowledge, no report describing the cause of staple malformation (staples not forming the ''B'' shape) exists.…”
mentioning
confidence: 79%
“…Because ischemic leaks are known to occur 5-7 days postoperatively, when wound healing is between the inflammatory and fibrotic phases, the most common causes of the vast majority of leaks, which occur within 48 h, are mechanical [26]. This provides a rationale for buttressing materials, which do not impart a decreased risk of leakage due to ischemia, but do decrease the risk of mechanical failure [50]. Most [6][7], but not all [31], studies have found that buttressing materials increase burst pressure.…”
Section: Etiology Of the Leaksmentioning
confidence: 96%
“…Although hand-sewn end-to-end anastomosis has been representative of intestinal anastomosis, the role of functional end-to-end anastomosis [1] using an automatic linear stapler is rapidly being established. Functional end-to-end anastomosis has been shown to be safe and has become quite popular in clinical settings [2,3].…”
Section: Introductionmentioning
confidence: 99%